1985
DOI: 10.1248/bpb1978.8.726
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of tetrachlorobiphenyls with isolated rat liver mitochondria.

Abstract: A comparative study of the effects of tetrachlorobiphenyls (TCBs) on the succinate-supported respirations of rat liver mitochondria was made, and some differences in effects caused by the different chlorine positions of the biphenyl rings were clarified. The inhibitory actions of 2,3,2',3'-,2,4,2',4'-, and 2,5,2',5'-TCBs on both state 3 and uncoupler-stimulated respirations were potent, while those induced by 2,6,2',6'-, and 3,4,3',4'-TCBs were weak. 2,3,2',3'-,2,4,2',4'-,2,5,2',5'-, and 2,6,2',6'-TCBs stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The 2,2′‐3,3′‐2,2′‐4,4′ and 2,2′‐5,5′ tetrachloro biphenyls (TCBs), as in the case of SN, are inhibitors of the succinate dehydrogenase, and complex I and cytochrome oxidase were unaffected [16]. Other authors [17] found that not only the respiratory chain, but also the phosphorylation system is inhibited with 20 n mol TCB/mg protein, while the same dose increases the membrane leak.…”
Section: Resultsmentioning
confidence: 99%
“…The 2,2′‐3,3′‐2,2′‐4,4′ and 2,2′‐5,5′ tetrachloro biphenyls (TCBs), as in the case of SN, are inhibitors of the succinate dehydrogenase, and complex I and cytochrome oxidase were unaffected [16]. Other authors [17] found that not only the respiratory chain, but also the phosphorylation system is inhibited with 20 n mol TCB/mg protein, while the same dose increases the membrane leak.…”
Section: Resultsmentioning
confidence: 99%
“…These observations provide further evidence for the hypothesis that ortho-substituted PCBs disrupt the structure of cell membranes in a relatively non-specific fashion, whereas there is little or no effect of the coplanar congeners. Previously, Nishihara et al (1985) have shown disruption of mitochondrial membranes by orthosubstituted PCBs. Dose-dependent increases in membrane fluidity in rat renal tubular cell cultures following exposure to Aroclor 1238 has been reported (LopezAparicio et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Interruption of [Ca 2+ ] i homeostasis induced by orthosubstituted PCBs has been reported in various cell types and models. Nishihara et al (1985) have shown that nonplanar tetrachlorobiphenyls alter calcium homeostasis by modulation of membrane integrity in isolated rat liver mitochondria. Wong et al (1997) demonstrated a rise in [Ca 2+ ] i levels in neurons and proposed that the calcium came from ryanodine sensitive-stores in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…As examples, cadmium has been shown to be an uncoupler of oxidative phosphorylation at con-*To whom correspondence may be addressed. Nishihara et al [5] state that 3,4,3',4'-TCB is a coplanar molecule due to the chlorine atoms in the para, para' positions, increasing the double bond character of the C(1)-C(1') bond. Shannon's current address is School of Public and Environmental Affairs, SPEA 322, Indiana University, Bloomington, Indiana 47405. centrations up to 33 p M , and inhibits mitochondrial respiration at higher concentrations [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the coplanarity of tetrachlorobiphenyls (TCBs) has been shown to affect their toxicity to rat liver mitochondria. Nishihara et al [5] state that 3,4,3',4'-TCB is a coplanar molecule due to the chlorine atoms in the para, para' positions, increasing the double bond character of the C(1)-C(1') bond. This coplanar TCB did not produce uncoupling action in mitochondria, whereas TCBs with chlorine atoms in ortho, ortho' positions were shown to produce uncoupling ef-fects.…”
Section: Introductionmentioning
confidence: 99%